SALIVARY PROFILE AND IDENTIFICATION OF EXISTING CANDIDA sp OF AN INSTITUTIONALIZED ELDERLY POPULATION IN JAKARTA: PROFIL SALIVA DAN IDENTIFIKASI KEBERADAAN CANDIDA sp PADA LANSIA DI PANTI JOMPO DI JAKARTA - Febrina Rahmayanti; Yuniardini Septorini Wimardhani; Indriasti Wardhany (TALENTA, 2013)
Saliva plays an important role to protect oral and dental health, in maintenance oral microflora balance. In elderly, disease, and medications usually influence the saliva. The purpose of this preliminary study was to investigate salivary profile, oral symptoms of dryness, and existing of Candida sp of an institutionalized elderly in Jakarta, Twenty seven (27) elderly (17 men and 10 women) were examined in a cross sectional study. Unstimulated whole saliva was collected for 5 minutes, according to published protocol, and then salivary flow rate and pH were measured. Candida sp were cultured in CHROM agar. The yeasts were counted and identified. Oral symptom or complaints of oral dryness, and burning or itching were recorded with an interview. Data of systemic conditions and medication the used were obtained from the medical record. Eighteen (66.7%) CHROM agar plates were Candida sp positive cultured, and about 61.1% subjects’ salivary pH were below normal range. Twenty one (77.8%) subjects had oral symptom and complain about oral dryness, even thought the salivary flow rate were in normal range. In this study, C.albicans is not the most frequently found colonized. About 72% were identified not C.albicans. This study suggests that, in elderly which salivary pH was below normal range have greater opportunistic infected by Candida sp. It can be concluded that, the result did not confirm a significant difference between subjects’ data and salivary profile concentration. The mycological finding Candida albicans is not the most frequently found colonized in this elderly population. Further study which lagger elderly population and might give deeper insights of salivary profile in this population.